Pre-eclampsia in Tanzania and Norway. Differences and similarities in follow-up and treatment, and how this affects maternal and perinatal/neonatal Health. - A combined literature and case study - Håpnes, May-Helen (UiT Norges arktiske universitet, 2014)
I followed up a total of 6 patients at the University Hospital of Northern Norway in Tromsø and 2 patients at Haydom Lutheran Hospital in Tanzania. I also collected information from a birth protocol at the University Hospital of Norway, Tromsø, and collected information about their guidelines in these two countries. Comparison between the two countries show that the guidelines were somewhat the same, but it is more difficult to follow-up patients in Tanzania due to more challenges in great travel distance, expensive costs of care and lower socioeconomic standard. Because of lower socioeconomic standard in Tanzania, both the mother and the foetus have a worse outcome compared to Norway, and that can also be due to home deliveries. They used somewhat the same medications in Norway and Tanzania, but it was some small differences in which drug they preferred to use.